Any good thing - Mangan, Andrew Nicholas, author; Levy, E. J., advisor; Doenges, Judy, committee member; Khrebtan-Hörhager, Julia, committee member (Colorado State University. Libraries, 2016)
This thesis is titled after its first story but also functions the primary theme of the collection itself: Each character is in casting around desperately for “any good thing” in their lives. These “good things” range from monetary salvation, to the mitigation of loneliness, to escape from someone toxic. The arc of the collection as a whole is that of people identifying their conditions, trying to rescue themselves from them, then finally doing so in complicated ways.